[Aerial view of Cal Poly Campus] (1954)
View of main campus, Dexter Library, Administration Building, Poly Ninos (Vetville), Poly Vue Trailers, North Mountain, construction of Science Building - looking east at Poly "P". See also http://digital.lib.calpoly.edu/rekl-5216 and http://digital.lib.calpoly.edu/rekl-3470